O1B.3 Hyperactivity disorder in children was related to maternal employment status during pregnancy and postpartum depressive symptoms: a prospective cohort study. (April 2019) - Shih, Ping; Huang, Ching-Chun; Chiang, Tung-liang; Chen, Pau-Chung; Guo, Yue-Liang Leon
Abstract : Background: Attention-deficit/hyperactivity disorder (ADHD) is one of the most common neurobehavioral disorders globally. Although some investigations implied a relationship between ADHD and maternal psychosocial stress exposure during pregnancy, little is known about the effects of maternal occupational exposure and even postpartum mental health. This study aimed to investigate whether maternal employment status during pregnancy and postpartum depressive symptoms are related to offspring hyperactivity, one of the key early symptoms of children ADHD. Methods: Taiwan Birth Cohort Study recruited representative mother-infant pairs, as a result of approximately 12% of all deliveries in 2005 using multistage stratified sampling. Employment status with or without job stress during pregnancy and postpartum depressive symptoms were inquired when the child was six months of age by face-to-face interview. Ever having hyperactivity syndrome as evaluated by physicians, psychologists, or special educators was inquired when the child was eight years of age. Factors of hyperactivity, including maternal employment, job stress, and postpartum depression were studied by adjusted odds ratios (aORs) and 95% confidence interval (CI) using logistic regression, adjusting for gender, urban/rural residence, birth season and household income. Results: 18 215 mother-infant pairs were included in the final analysis, where 421 (2.3%) of children had been diagnosed as having hyperactivity before 8 years of age. Comparing to mothers employed and without job stress during pregnancy, the aOR (95% CI) of child hyperactivity was 1.47 (95%CI: 1.12, 1.94) for mothers with job stress and 1.43 (95%CI: 1.12, 1.84) for mothers with no employment during pregnancy, respectively. Besides, children were 1.36 (95% CI: 1.07, 1.73) times more likely to receive an ADHD diagnosis if their mother experienced postpartum depressive symptoms. Conclusions: In this prospective birth cohort study, mothers' employment status, job stress during pregnancy, and postpartum depressive symptoms were risk factors for the occurrence of hyperactivity in their children.